Pembelajaran Aswaja Berbasis Nilai-Nilai Kitab Ta’lim Muta’allim: Studi Kasus di Madrasah Aliyah Darut Taqwa Sooko Wringinanom Gresik - Heri Darmawansah; Rahmat (eJurnal Al Musthafa, 2021)
The purpose of this study is to describe and analyze Aswaja Learning Based on the Values ​​of the Ta’lim Muta’allim Book at Madrasah Aliyah Darut Taqwa Sooko Wringinanom Gresik, to describe and analyze the implications of Aswaja Learning based on the values ​​of the Ta’lim Muta’allim Book at Madrasah Aliyah Darut Taqwa Sooko Wringinanom Gresik. To find Aswaja Learning Based on the Values ​​of the Book of Ta’lim Muta’allim, the researcher used a qualitative research method with a case study approach by collecting data, then analyzing and making conclusions from the data in the field that had been obtained.The findings of this study are: 1) Aswaja learning based on the Ta’lim Muta’allim book, the researchers conclude, a) Madrasah Aliyah Darut Taqwa Sooko Wringinanom implements or combines the national curriculum with Islamic boarding school materials, b) The method used in aswaja learning is based on the values ​​of the Ta’lim Muta’allim book is the bendongan method by which the teacher reads, translates, and explains sentence by sentence so that students more quickly understand the meaning and values ​​contained in the Ta’lim Muta’allim book, and c) Aswaja learning based on the values ​​of the Ta’lim Muta’allim is one of the extra subjects at Madrasah Aliyah Sooko Wringianom, and 2) the implications of Aswaja learning based on the values ​​of the book Ta'lim Muta'allim at Madrasah Aliyah Darut Taqwa Sooko Wringinanom Gresik .the researchers concluded, a) Correcting the moral crisis to students with Aswaja learning guidelines based on the values ​​of the Ta’lim Muta’allim book, b) The teacher being an example or role model for students, and c) Conducting evaluations on students about the extent to which they which is an understanding of the values ​​contained in the book of Ta’lim Muta’allim by way of assessment in the form of daily tests and semester tests such.